Kinematic step-parameters and triple jump performance in female youth athletes - Jaitner, T.; van Haren, A.; Hahn, D. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Especially in youth athletes, the step in triple jumping is considered to be crucial since it rather serves as a transition phase between hop and jump than as a major contributor to the overall distance (Hay, 1993). This is further supported by observations that during the step youth athletes do not perform a jump but a running step, which is in accordance with the suggestion of Hay and Miller (1985) that a more accentuated step results in a greater overall distance. Therefore, the aim of this study was to investigate the relationship between kinematic step-parameters and step-distance as well as their contribution to the overall performance. METHODS: Distances and contact times of hop, step and jump as well as flight times of hop and step were recorded from 129 jumps of 32 female youth triple jumpers using Optojump next™ (Microgate, Italy) during regional and national championships. Mean approach velocity (va) was determined between 6m and 1m before take-off. Actual overall distance, phase distances and phase ratios (% of overall distance) were determined according to Hay (1993). Step flight ratio and the change in horizontal velocity from hop to step ( v) were also calculated. Several correlation coefficients between the kinematic parameters obtained were determined according to Pearson and Spearman depending on normal distribution. RESULTS: Mean and SD for va, overall and phase distances reached 7.7±.5m/s, 10.69±.63m, 3.89±.31m (hop), 2.62±.48m (step), and 4.18±.39m (jump), respectively. Mean phase ratios were 36±2% (hop), 24±4%(step), 39±4%(jump) . Step flight ratio achieved 49±13%, while v was -1.5±3.8m/s. Overall distance showed moderate correlations to va (r=.443) and stepdistance (r=.548) but a strong correlation to hop-distance (r=.841). Further did step-distance inversely influence jump-distance (r=-.61). Step-parameters phase ratio, v, flight ratio were highly to moderately related to step distance (r=.944, -.565, .684) but could not predict overall triple jump performance (r .4). DISCUSSION: According to our results, hop distance had the greatest influence on triple jump performance. However, also the step significantly affected overall distance, and kinematic step parameters revealed that a good step is mainly characterized by a high phase ratio but also by a reduction in velocity from hop to step and a high flight ratio. This points towards a jump-accentuated step rather than representing a running step used as transition phase from hop to jump. In future, multi-regression analysis is needed to explain the more complex interaction of the parameters that contribute to greater performances.